IMPLEMENTATION STRATEGY IBADURROCHMAN VALUES IN SHAPING THE CHARACTER OF SANTRI AT THE ANWARUL HUDA ISLAMIC BOARDING SCHOOL IN MALANG - Havid, Muhammad; Fahriyan, Wahyu (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research aims to describe the use of strategies applied in implementing Ibadurrachman values to shape the character of the students of the Anwarul Huda Islamic boarding school. This research adopts a descriptive qualitative approach. The Anwarul Huda Islamic Boarding School employs a comprehensive strategy to shape the character and spirituality of its students, rooted in the values of Ibn Aqil, known as Ibadurrachman. These values encompass spiritual, social, and academic aspects, guiding students towards holistic development. Through a participatory approach and holistic learning, the school fosters leadership skills and empathy among students. Curriculum development integrates Ibadurrachman's values, aiming to produce individuals capable of contributing positively to society. The study employs a qualitative descriptive method, focusing on the school's implementation strategy and its impact on student character. Strategies include routine activities, environmental conditioning, and spontaneous activities, aimed at instilling values like discipline, simplicity, and responsibility. The integration of these strategies into daily life aims to cultivate habits aligned with Ibadurrachman's values, fostering character development among students. Overall, the school's approach emphasizes the importance of consistent effort and self-awareness in character formation, drawing inspiration from the exemplary character of Prophet Muhammad and contemporary scholars like KH. Moh. Baidowi Muslich.